The Essence and Characteristics of Outsourcing (Economic journal of Lesya Ukrainka Volyn National University, 2016)
On the basis of analysis of the literature on the issue of outsourcing research and practice of national companies which use outsourcing, it was improved and enriched concepts and categories of the theory of management outsourcing. In particular, the author suggested the existing approaches to the definition of outsourcing divided into four groups: target, process, strategic and stakeholder, and singled out the main features of modern outsourcing. The author clearly distinguishes the concept of outsourcing the supply of resources, vertical integration and also underlines the main sign outsourcing that this type of business activities. Thus, outsourcing is kind of business activity, which is the reorganization of business processes by involving stakeholders in the implementation of secondary and inefficient functions and concentration on key products. It was divided concept outsourcing, outsourcing service, outsourcing operations and outsourcing activities. Outsourcing as a phenomenon that led to revolutionary changes in the construction business processes of different areas of organizations also provoked a flow of a series of original concepts that are widely used businesses – is offshoring (offshoring), niashornh (nearshoring), crowdsourcing (crowdsourcing), multyysorsynh (multisourcing). In all these activities is the main mechanism of transmission outsourcing as part of other interested groups and scaling operations.
Keywords: outsourcing, service provider, enterprise, business process, management of outsourcing